HUBUNGAN ANTARA AKTIVITAS MEDIA SOSIAL TINGKAT PENGETAHUAN SEKSUAL REMAJA DI SMA DANUL FALAH - Purnasari, Henni; Triana, Hani; Sianipar, Imelda (Sekolah Tinggi Ilmu Kesehatan Dharma husada, 2025)
Currently, adolescence’s needs for information, education and service on reproductive health are still not met well. Teenagers frequently find discussing their sexuality issues or reproductive health to be awkward or taboo. However, because they are curious, they look for information. Teenagers frequently feel that their parents won't discuss sexuality issues with them, so they turn to friends or the media for support. The purpose from this research is to find is there any relation between the use of social media and adolescence’s sexuality knowledge level in Senior High School Danul Falah. The type of this research is descriptive correlation and use design study cross sectional. Total sampling in this research is 190 students on grade X Senior High School 5 Samarinda and sampling technique is Proportionate Stratified Random Sampling. The data analysis used to test the hypothesis is Chi-Square. The result of statistic test between the use of social media and adolescence’s sexuality knowledge level was obtained p-value 0.00 <(α) 0.05 then H0 rejected. It showed that statistically there was significant relationship between the use of social media and adolescence’s sexuality knowledge level in Senior High Schoo. There is significant relation between the use of social media and adolescence’s sexuality knowledge level in Senior High School.